Synthesis of Chlorinated Arenes and Hetarenes by One-Pot Cyclizations of 1,3-Bis-silyl Enol Ethers - Hassan, Zahid; Langer, Peter (Synlett, 2019)
This account describes our recent findings and progress in synthesizing chlorinated arenes and hetarenes by one-pot cyclizations of 1,3-bis-silyl enol ether derivatives. These reactions allow for the preparation of highly functionalized products with a high level of regioselectivity. The synthetic routes are cost-effective avoiding additional functionalization steps. The products are difficult to be accessed by other methods. The chlorine atom is of relevance in medicinal and agriculture chemistry. In addition, it allows further functionalizations by transition-metal-catalyzed cross-coupling reactions.1 Introduction2 Cyclizations of 2-Chloro-1,3-bis(silyloxy)-1,3-butadienes2.1 3,5-Dihydroxychlorophthalates2.2 2,4-Dihydroxy-homochlorophthalates2.3 2-(Arylsulfonyl)chloropyridines2.4 1-Azaxanthones3 Cyclizations of 4-Chloro-1,3-bis(trimethylsilyloxy)-1,3-butadienes3.1 3-Chlorosalicylates3.2 Functionalized Chlorobiaryls3.3 3-Chloro-5-(2-chloroethyl)-salicylates3.4 2,4-Dihydroxychlorobenzophenones4 Cyclizations of 2-Chloro-3-(silyloxy)-2-en-1-ones4.1 Functionalized Chlorophenols4.2 Functionalized Chlorinated Biaryls and Chlorofluorenones4.3 Functionalized Chlorochromenones4.4 Functionalized 3-(Methylthio)chlorophenols4.5 Functionalized 3-Chloromethylphenols5 Conclusions6 List of Abbreviations
Keywords: silyl enol ethers; one-pot cyclizations; chlorine; arenes; heterocycles; regioselectivity